2001
DOI: 10.1096/fsb2fj000324com
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor induces hyperproliferation and delays differentiation in a skin equivalent model system

Abstract: Keratinocyte growth factor (KGF) is a paracrine mediator of epithelial cell growth. To examine the direct effects of KGF on the morphogenesis of the epidermis, we generated skin equivalents in vitro by seeding human keratinocytes on the papillary surface of acellular dermis and raising them up to the air‐liquid interface. KGF was either added exogenously or expressed by keratinocytes via a recombinant retrovirus encoding KGF. KGF induced dramatic changes to the 3‐dimensional organization of the epidermis inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 43 publications
5
30
0
Order By: Relevance
“…As far as we know, this is the first time that a clinical description of a cutaneous reaction related to palifermin has been supported by histological analysis, whose most striking feature is the presence of large keratinocytes, suggesting a direct effect of palifermin in cell proliferation and differentiation, consistent with previous studies that showed these changes in a skin equivalent model system when treated with keratinocyte growth factor (KGF) (Andreadis et al, 2001).…”
supporting
confidence: 89%
“…As far as we know, this is the first time that a clinical description of a cutaneous reaction related to palifermin has been supported by histological analysis, whose most striking feature is the presence of large keratinocytes, suggesting a direct effect of palifermin in cell proliferation and differentiation, consistent with previous studies that showed these changes in a skin equivalent model system when treated with keratinocyte growth factor (KGF) (Andreadis et al, 2001).…”
supporting
confidence: 89%
“…Accordingly, reproducibility between different laboratories becomes almost impossible (Faller & Bracher, 2002;Ng & Ikeda, 2011). To help address this issue, we used defined commercially manufactured media with the addition of three additives: KGF to promote keratinocyte proliferation and stratification (Marchese et al 1990;Andreadis et al 2001), ascorbic acid involved in epidermal differentiation (Savini et al 2002), and calcium, known to promote keratinocyte proliferation under 0.1 mM and to encourage keratinocyte differentiation at higher concentrations (Hennings et al 1980;Bikle, 2012). Thirdly, introducing hydrogels to create a full thickness skin model, primarily in the form of collagen-based materials from different sources such as rat, bovine or human, can generate batch variability (El Ghalbzouri et al 2005) and may introduce species-specific effects when combining animal and human materials.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results obtained in culture, the number of cycling keratinocytes (Ki67-positive cells) was diffusely upregulated (up to 15 times) in perilesional and nonlesional epidermis as well as in mucosa of all PV patients analyzed ( Figure 3B). Moreover, the proliferating Ki67-positive cells localized to basal and suprabasal layers, a typical feature of hyperproliferative epidermis (Andreadis et al, 2001). Despite this, differentiation markers were still expressed, but their expression pattern was disrupted in particular in patients with longstanding disease (Supplementary Figure 5).…”
Section: The Status In Pv Patients Reflects the Findings In Cultured mentioning
confidence: 99%